N6-Methyladenosine Modification Participates in the Progression of Hepatitis B Virus-Related Liver Fibrosis by Regulating Immune Cell Infiltration - Zhao, Tong; Qi, Jianni; Liu, Tiantian; Wu, Hao; Zhu, Qiang (Frontiers in Medicine, 2022)
Aim: N6-methyladenosine (m6A) modification have been demonstrated to play an important part in hepatitis B virus (HBV) infection and immune response. This study aims to further investigate whether m6A modification plays an important role in the progression of HBV-related liver fibrosis through the regulation of immune cell infiltration. Methods: 124 chronically HBV infected cases were obtained from the Gene Expression Omnibus database. 489 m6A-and-stage related genes were selected to be associated with m6A modification and stage of liver fibrosis. Based on these genes, we identified two distinct gene clusters, gene clusterA and B. The immune characteristics of the two clusters were comprehensively compared.m6A-S score was constructed as a quantification of individual m6A status. The correlations between m6A regulators and infiltrating immune cells were examined and compared in different pairs of groups with various m6A traits. Results: Biological functions, immune cell infiltration and cytokines expression were compared between the two gene clusters proving that gene clusterB was more immune active and had more advanced liver fibrosis stage. m6A-S score was associated with immune infiltration and the progression of liver fibrosis. Five different grouping conditions with different m6A traits were set up. According to the intersection of significant genes and cells, ALKBH5 interacting with macrophage and WTAP interacting with nature killer T cell may be key points in the progress of liver fibrosis. Conclusions: m6A modification is closely related to immune cell infiltration and fibrosis stage of chronic HBV infected liver tissue. It provides us a better understanding of the progression of liver cirrhosis via evaluating m6A modification pattern and immune infiltration characteristics.